Aversive emotion rapidly activates orexin neurons and increases heart rate in freely moving mice - Akira Yamashita; Shunpei Moriya; Ryusei Nishi; Jun Kaminosono; Akihiro Yamanaka; Tomoyuki Kuwaki (Molecular Brain, 2021)
Abstract The perifornical area of the hypothalamus has been known as the center for the defense response, or fight-or-flight response, which is characterized by a concomitant rise in arterial blood pressure, heart rate, and respiratory frequency. It is well established that orexin neurons, which are located in this region, play a critical role in this response. In this study, we further examined this role by recording orexin neuronal activity and heart rate in freely moving mice using an original dual-channel fiber photometry system in vivo. Analysis of orexin neuron activity in relation to autonomic responses to aversive stimuli revealed a rapid increase in neuronal activity just prior to changes in heart rate. In addition, we examined whether orexin neurons would be activated by a conditioned neutral sound that was previously associated with aversive stimulus. We show that the memory of the aversive stimulus activated orexin neurons and increased heart rate. Our data suggest that orexin neurons are a key component linking aversive emotions to autonomic defense response. Our data also suggest that targeting orexin neurons may enable treatment of psychiatric disorders associated with chronic stress and traumatic memories.